Multi-stage taxation by subnational governments: Tax incidence and Leviathan taxation - Cont, Walter Alberto (2016)
This paper analyzes multi-stage taxation by provinces in a federal country, using a novel two-good, two-province, successive-oligopoly heterogeneous-product Bertrand competition model, where each producer is located in a province and sells its product through exclusive retailers located in both provinces. The producer-retailer setup allows provincial governments to raise taxes on upstream and downstream transactions. First, we analyze tax incidence results and emphasize the importance of the degree of downstream competition on the tax shifting. Second, we solve a non-cooperative revenue maximization problem and study the properties of the equilibrium taxes. We characterize the solution: either all tax rates are positive or one province drops one tax rate. This way, the full-tax solution dominates upstream and downstream taxation. Also, the non-cooperative solution implies over-taxation when compared with the cooperative solution.